PENINGKATAN HASIL BELAJAR PERMAINAN BOLA KECIL SISWA KELAS VB TUNARUNGU DENGAN MENGGUNAKAN PERMAINAN BOLA ADVENTURE DALAM PEMBELAJARAN PENJAS DI SDLB NEGERI PURBALINGGA TAHUN AJARAN 2013 / 2014 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the improvement of learning outcomes play small ball VB class deaf students using a ball game adventure in learning SDLB Purbalingga penjas in the academic year 2013/2014 . This study is an action research ( action research) because of research done to solve the problem of learning in the classroom . Observations on cycle 1 , ie psychomotor aspects gained 65.47 % , 80.95 % gain cognitive and affective aspects of acquiring 100 % . In the first cycle the average value reached 78.92 class that meets both criteria . While the results of observations of cycle 2 , the psychomotor aspects of gaining 74.99 % , 90.47 % gain cognitive and affective aspects of acquiring 100 % . . In the second cycle the average value reached 84.4 classes that meet the criteria very well. Based on the above results , concluded that Ball Adventure games can improve learning outcomes of small ball . Therefore Penjasorkes teachers are advised to use the game as an alternative learning Adventure Ball Small Ball in SDLB.